STATUS PENGUASAAN TANAH TEPI PANTAI (STUDI DI KABUPATEN PAMEKASAN) - Sudahnan Sudahnan (Perspektif, 2006)
Having a piece of land representing a desire all person, but owning a piece of land by people require to it know. Let property so that clear. Having a piece of lands di edge coast which conducted agglomeration by resident of countryside. Kramat district Talanakan Sub—Province Pamekasan need in knowing its status so that its enterpasing becoming clear and as according to legislation going into effect. To clarify status punish domination of land grounds ashore, hence the importance of request permiting to relevant institution last in registering to. Badan Pertanahan Nasional (BPN), so that its status become clear become property.